The works of John Robinson, pastor of the pilgrim fathers - Robinson, John (J. Snow, 1851)
I. Memoir. Dr. Allen's Descendants of Robinson. Essays, or, Observations divine and moral. Defence of the doctrine propounded by the Synod of Dort.--II. A justification of separation from the Church of England, against Mr. Bernard's invective, entitled the Separatist's schism.--III. A just and necessary apology. Two letters on Christian fellowship. On religious communion, private and public. The people's plea for the exercise of prophecy. On the lawfulness of hearing ministers in the Church of England. A letter to the Congregational church in London. An appeal on truth's behalf. An answer to a censorius epistle. A catechism. Appendix: The church in Southwark, by Rev. John Waddington. The exiles and their churches in Holland.